The Properties and Activity of TiO2-based Nanorods as an Anti-Fouling Agent and a Photocatalyst - Wahyuni, Sri; Kartini, Indriana; Kadarwati, Sri (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
The properties and activity of TiO2-based nanorods as an antifouling agent and a photocatalyst for the catalytic degradation of methylene blue (MB) have been investigated. A modification of TiO2 with SiO2 was first carried out to enlarge the surface area. In order to enhance the TiO2 photo response to the visible light region, a further modification of TiO2-SiO2 (TS) composites with polyaniline (PANI) was also conducted. The nanorod TiO2 exhibited an anatase structure based on the diffraction patterns. The TEM images showed that some TiO2 molecules were attached around SiO2 with a random orientation. The TiO2-SiO2-PANI (TS-PANI) exhibited the largest specific surface area (SBET) of about 256.85 m2/g. The profile on the AFM images of the composites showed that the nano-roughness of the coatings was confirmed. The photocatalytic activity was evaluated through the decomposition of MB both on the powder and the coated composites. The photocatalytic activity on the coatings was verified due to further application as anti-fouling coatings involving photocatalytic mechanism. The decomposition of MB using TS-PANI powder and TS-PANI coating composites was 89.5% and 90.2 %, respectively, with the irradiation time on the coatings was 20 min longer. The anti-fouling activity through the photocatalytic mechanism and nano-roughness surface was confirmed by the inhibition of barnacle growth on the teakwood surface immersed for two months in the sea.